2018
DOI: 10.1186/s12885-018-4178-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic implications of ribosomal protein transcript expression patterns in human cancers

Abstract: BackgroundRibosomes, the organelles responsible for the translation of mRNA, are comprised of four rRNAs and ~ 80 ribosomal proteins (RPs). Although canonically assumed to be maintained in equivalent proportions, some RPs have been shown to possess differential expression across tissue types. Dysregulation of RP expression occurs in a variety of human diseases, notably in many cancers, and altered expression of some RPs correlates with different tumor phenotypes and patient survival. Little work has been done,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 56 publications
5
72
0
Order By: Relevance
“…It could be due to the crucial role of RPs in cell growth and proliferation propagated through protein synthesis. In cancers, ribosomal biosynthesis increases to meet the requirement of rapidly growing/proliferating cells (48). Some RPs take part in extra-ribosomal functions involved in tumorigenesis, immune cell signalling, and development and regulating diseases through translocation across the nuclear pore complex (49).…”
Section: Discussionmentioning
confidence: 99%
“…It could be due to the crucial role of RPs in cell growth and proliferation propagated through protein synthesis. In cancers, ribosomal biosynthesis increases to meet the requirement of rapidly growing/proliferating cells (48). Some RPs take part in extra-ribosomal functions involved in tumorigenesis, immune cell signalling, and development and regulating diseases through translocation across the nuclear pore complex (49).…”
Section: Discussionmentioning
confidence: 99%
“…For many years, scientists believed that unassembled RPs undergo rapid degradation. However, recent findings support the idea that extracellular or intracellular stimuli induce ribosomal stress, which disturbs ribosomal biogenesis followed by the accumulation of free RPs (Dolezal, Dash, & Prochownik, 2017). RPs participate in multiple extraribosomal functions, including DNA damage repair, apoptosis, cell proliferation and differentiation, drug resistance, and cell migration and invasion (Xu, Xiong, & Sun, 2016).…”
Section: Introductionmentioning
confidence: 93%
“…RNAseq data were obtained from the 10,227 newly diagnosed and previously untreated cancers of all stages, comprising 34 distinct types, currently maintained in TCGA along with pertinent clinical and demographic data. FPKM-UQ were obtained from the TCGA GDC PANCAN dataset and through the University of California Santa Cruz UCSC Xenabrowser as previously described [9,12,13]. Expression values were initially stored as the log 2 of the incremented-by-one FPKM-UQ value.…”
Section: Tumor Selectionmentioning
confidence: 99%
“…In murine models of hepatoblastoma and hepatocellular carcinoma (HCC), we have previously observed that most transcripts encoding the 80 proteins comprising the 40S and 60S ribosomal subunits were significantly increased relative to those in normal livers [9,10]. Because these increases were not uniform, the overall transcript expression patterns were altered as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation